THE TARKHANIAN-KARAGANIAN STAGE IN DEVELOPMENT OF THE EUXINIAN-CASPIAN BASIN (EASTERN PARATETHYS). PART 1: TARKHANIAN - Goncharova I.A.; Khondkarian S.O.; Shcherba I.G. (My University, 2001)
Evolution of the Euxinian-Caspian basin (Eastern Paratethys since the Oligocene) during the Tarkhanian (terminal early-initial middle Miocene) is considered, and its interrelations with the Alpine-Carpathian (Western Paratethys), Central Iranian, and East Mediterranean basins are discussed. The article includes the map of current distribution of Chokrakian deposits and their continental analogues, and the paleogeographic map for the Chokrakian time, where geological history of the Transcaspian region, Paleo-Don delta area, and Caucasus region are anew interpreted. Supplementary palinspastic profiles illustrate the peculiar morphology and bathymetry of the Chokrakian basin.
Keywords: Euxinian-Caspian basin; Tarkhanian; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен